Review of Fish Feed Forms, Processes, and Their Purpose - Andriani, Yuli; Putri, Ismi Nabila; Aufa, Indrawan; Isya, Muhammad Filah; Nofatari, Nofatari; Aisyah, Aisyah (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
Fish feed is critical to the success of aquaculture as it fulfills nutritional needs, promotes growth, and improves fish health. Several feed forms are used routinely, such as flake, pellet, and cake, each with its characteristics and applications, depending on the fish species and growth stage. Flake feed is a good choice for ornamental fish and small fish that consume on the surface or in the water column because it allows it to float longer on the water surface, making it easier for small fish to consume. Cake-shaped feed is soft, denser, and has a distinctive cake aroma. Cake-shaped feed is usually used for larval-stage fish species with small mouth openings. In addition, pelleted feed, available in various sizes and densities, is becoming more popular in consumer fish farming because it is easy to apply and can meet balanced nutritional needs, especially for sizeable juvenile fish. Pellets can be adjusted to match the water density for fish feeding at the water's top, column, or bottom. Therefore, it is crucial to know the forms of feed and their uses so that farmers can choose the optimal feed for their fish by understanding the characteristics and applications of each type of feed.